Reduction of system of partial derivatives with nilpotent matrix - Jurgaitis, Donatas; Janavičius, Arvydas-Juozapgs (Lietuvos matematikos rinkinys, 2000)
In this paper we explain the method of squaring of the partial derivatives system with nilpotent matrix into the system with simpler matrix next to the solving function. Asymptotical solutions of this new system can be found using the method of gradual rows.